Covalently bound DNA on naked iron oxide nanoparticles: Intelligent colloidal nano-vector for cell transfection - Magro, Massimiliano; Martinello, Tiziana; Bonaiuto, Emanuela; Gomiero, Chiara; Baratella, Davide; Zoppellaro, Giorgio; Cozza, Giorgio; Patruno, Marco; Zboril, Radek; Vianello, Fabio (Biochimica et biophysica acta. General subjects, 2017)
BACKGROUND: Conversely to common coated iron oxide nanoparticles, novel naked surface active maghemite nanoparticles (SAMNs) can covalently bind DNA. Plasmid (pDNA) harboring the coding gene for GFP was directly chemisorbed onto SAMNs, leading to a novel DNA nanovector (SAMN@pDNA). The spontaneous internalization of SAMN@pDNA into cells was compared with an extensively studied fluorescent SAMN derivative (SAMN@RITC). Moreover, the transfection efficiency of SAMN@pDNA was evaluated and explained by computational model. METHODS: SAMN@pDNA was prepared and characterized by spectroscopic and computational methods, and molecular dynamic simulation. The size and hydrodynamic properties of SAMN@pDNA and SAMN@RITC were studied by electron transmission microscopy, light scattering and zeta-potential. The two nanomaterials were tested by confocal scanning microscopy on equine peripheral blood-derived mesenchymal stem cells (ePB-MSCs) and GFP expression by SAMN@pDNA was determined. RESULTS: Nanomaterials characterized by similar hydrodynamic properties were successfully internalized and stored into mesenchymal stem cells. Transfection by SAMN@pDNA occurred and GFP expression was higher than lipofectamine procedure, even in the absence of an external magnetic field. A computational model clarified that transfection efficiency can be ascribed to DNA availability inside cells. CONCLUSIONS: Direct covalent binding of DNA on naked magnetic nanoparticles led to an extremely robust gene delivery tool. Hydrodynamic and chemical-physical properties of SAMN@pDNA were responsible of the successful uptake by cells and of the efficiency of GFP gene transfection. GENERAL SIGNIFICANCE: SAMNs are characterized by colloidal stability, excellent cell uptake, persistence in the host cells, low toxicity and are proposed as novel intelligent DNA nanovectors for efficient cell transfection.
Keywords: Fluorescent nanoparticles; Microscopy, Electron, Transmission; velikost částic; Gene Transfer Techniques; Particle Size; biofyzikální jevy; Nanoparticles; Biophysical Phenomena; transfekce; Transfection; železité sloučeniny; DNA; lidé; technika přenosu genů; nanočástice; koloidy; Mesenchymal stem cell; genetické vektory; Green fluorescent protein (GFP); plazmidy; DNA chemisorption; Plasmids; transmisní elektronová mikroskopie; Magnetic nanoparticles; Genetic Vectors; Ferric Compounds; Colloids; Humans